THE CONTRIBUTION OF COHESIVE TIES TO THE COHESION OF EFL STUDENTS' EXPOSITORY WRITING - Asikin, Nida Amalia (2014)
This thesis is a descriptive case study concerning cohesion in EFL students' expository writing. The study explores the use of cohesive ties in students' writing, the contribution of cohesive ties to students' writing and the ways students were exposed to the use of cohesive ties in their writing. The data of the study are nine expository texts produced by nine twelfth-year students of a senior high school in Kuningan. The study used a qualitative research design. There were two data collection procedures applied in this study, i.e. document analysis and interview. The data from students' texts were analyzed on the basis of the concept of cohesive ties by Haliday and Hasan (1976), i.e. reference, substitution, ellipsis, conjunction, and lexical cohesion. The results of the study revealed that from the nine texts, cohesive ties were used 509 times and there were only four types of cohesive ties - reference, substitution, conjunctions, and lexical cohesion - found in the students' texts. It is also found that cohesive ties contribute to the process of participants' tracking, the process of pointing to something within and outside the text, the process of substituting one item by another, the process of connecting the preceding part with the previous one systematically, and the process of investigating the repetitive sequences of lexically linked items and their relations to the core. Moreover, the data from interview revealed that there are two ways the students exposed to cohesive ties. First, the students were given direct explanation. Second, they were given correction without explanation. Overall, it is inferred that the contribution of the use of cohesive ties to the text cohesion is not high, and this seems to result from insufficient practice of how to write cohesively. For that reason, it is suggested that students be exposed to the use of appropriate cohesive ties in their writing.